Developing Metacompetence in Low Intensity Cognitive‐Behavioural Therapy (CBT) Interventions: Evaluating a Self‐Practice/Self‐Reflection Programme for Experienced Low Intensity CBT Practitioners. (October 2015) - Thwaites, Richard; Cairns, Laura; Bennett‐Levy, James; Johnston, Laura; Lowrie, Ria; Robinson, Andrea; Turner, Melanie; Haarhoff, Beverly; Perry, Helen
Abstract : Self‐practice/self‐reflection (SP/SR) is a targeted training and professional development strategy in which clinicians practice cognitive‐behavioural therapy (CBT) techniques and processes on themselves and then working through a structured process of self‐reflection. Previous studies with CBT trainees and experienced mental health practitioners have found that SP/SR or experiencing CBT "from the inside out" has been perceived by participants as increasing competency in a number of important areas and increasing therapist flexibility and artistry. Low intensity (LI) practitioners are identified as a relatively new addition to mental health service delivery in the UK. These workers are differentiated from traditional mental health practitioners by a shorter training period, the delivery of a circumscribed number of CBT interventions, and a very high weekly patient load. This study, the first of its kind, reports outcomes from an SP/SR programme undertaken by seven experienced LI CBT practitioners. Participants used the following measures to track their experience of the programme: time spent on programme, personal‐ and therapy‐related belief rating, goals attained, and perceived skill rated for average and most difficult patients. Results showed a positive change in work‐related skill and behaviour change, particularly when working with the more difficult patients. The findings are consistent with those found in other groups of therapists (e.g., trainee CBT therapists and highly experienced CBT therapists), suggesting that SP/SR may be a valuable addition to LI intensity training and professional development. These findings are discussed in the context of the particular needs of LI practitioners.